(untitled) (Bangladesh Journal of Agriculture, 2025)
A field experiment was conducted at Horticulture farm of Sher-e-Bangla Agricultural University, Dhaka, during the Rabi season of November, 2021 to April, 2022 to study the effects of different level of sulphur and boron on the yield and yield components of fenugreek (Trigonella corniculata) seed. The experiment consisted of two factors: Factor A: 4 Levels of sulphur (S); T0 = S0 kg ha-1, T1 = S10kg ha-1, T2 = S15kg ha-1, T3 = S20kg ha-1 and Factor B: 4 levels of boron (F); F0 = B0kg ha-1, F1 = B1.0kg ha-1, F2 = B1.5kg ha-1, F3 = B2.0kg ha-1. The experiment was laid out in randomized complete block design (RCBD) with three (3) replications. Data on different growth, yield contributing and yield parameter of fenugreek were recorded and significant variation was observed from different treatments. T3F3 treatment showed better performance over other treatment combination. Maximum plant height (50.08 cm), number of primary branches per plant (10.41), secondary branches per plant (5.09), number of seeds per pod (8.91), number of pod per plant (1192.30), weight of seeds per plant (2.50 g), weight of seed per plot (75.00 g), maximum seed yield per hectare (625.00 kg) was obtained from T3F3 treatment combination. Bangladesh J. Agri. 2024, 49(2): 79-86